The "dominant identity" postulate - Jakovljević, Dragan (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
In recent years, hardly any other intellectual has presented theses about the identity of Montenegro with such emphasis in public, such as the president of CANU, prof. Dragan Vukcevic. Admittedly, he did this in a scientifically non-systematized form, namely within the framework of a series of interviews and appropriate speeches. His initial thesis is that in all considerations of a given profile, one should start from the "triad" State-Constitution-Citizen, within which all the important contents for the given two fundamental issues could and should be considered.